Mapping an Arabian oasis: first results of the UCOP systematic survey of al‑ʿUlā (AlUla) Valley (2019–2021) - Charbonnier, Julien; Kanhoush, Yasmin; Gravier, Julie; Gourret, Gaël; Achouche, Imane; Bernollin, Vincent; Boudia, Sofian; Bucci, Walter; Chiti, Barbara; Clauss-Balty, Pascale; et al. (Proceedings of the Seminar for Arabian Studies, 2023)
Funded and steered by the French Agency for AlUla Development (Afalula) on behalf of the Royal Commission for AlUla (RCU), the AlUla Cultural Oasis Project (UCOP), undertaken by Archaïos, aims at mapping and understanding the spatial organization of the al‑ʿUlā oasis (Kingdom of Saudi Arabia). The project’s methodology includes a systematic foot survey of cultivated areas in al‑ʿUlā Valley, the vectorization of identified archaeological structures on the GIS using high-resolution orthophoto maps, as well as remote sensing on archive imagery. In the present paper we aim to fill the gaps in our knowledge of the understudied Islamic and pre-modern Arabian oases by presenting and proposing a preliminary analysis of the archaeological map of al‑ʿUlā Valley, resulting from the first five field seasons of UCOP (2019–2021). For this purpose, we will delineate the ‘historical oasis of al‑ʿUlā Old Town’ (i.e. the locale formed by al‑ʿUlā Old Town and associated gardens and fields, from their foundation in the middle Islamic period to the early twentieth century), provide a first study of its spatial organization, describe its components, and highlight the rapid growth of the gardens during the twentieth century. Ultimately, our objective is to contribute to the preservation and enhancement of this exceptional heritage, which is inseparable from the already protected al‑ʿUlā Old Town.